2008
DOI: 10.2106/jbjs.g.01676
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a System-Based Course in Musculoskeletal Medicine for Medical Students

Abstract: The main features of the course were: (1) an emphasis on both cognitive and process-based knowledge; (2) more contact hours and broader content than in previously described courses in musculoskeletal medicine; (3) the use of small groups to focus on problem-solving and physical examination competencies; (4) basic-science content directly related to clinical goals. These features might be used at other institutions that employ a system-based curriculum for the preclinical years to help improve competence in mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 9 publications
2
47
0
Order By: Relevance
“…Such action made an impact in the USA [20]. Bilderback noted a 77.8% pass rate after six weeks of a special system-based programme in orthopaedics [21]; 31.3% of Canadian medical schools have a mandatory clinical exposure to musculoskeletal education [2], unlike the Nigerian situation in which it is mandatory in all schools in our study. The corresponding authors' medical school has a ten day slot for orthopaedic education.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such action made an impact in the USA [20]. Bilderback noted a 77.8% pass rate after six weeks of a special system-based programme in orthopaedics [21]; 31.3% of Canadian medical schools have a mandatory clinical exposure to musculoskeletal education [2], unlike the Nigerian situation in which it is mandatory in all schools in our study. The corresponding authors' medical school has a ten day slot for orthopaedic education.…”
Section: Discussionmentioning
confidence: 98%
“…The range of scores was from 7% to 67%, with a mean of 28.9±10.6 and a median of 29 [interquartile range (IQR) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. The range of mean scores for each question was from 1.8% (question 11) to 89.9% (question 10) ( Table 1).…”
Section: Exam Scoresmentioning
confidence: 99%
“…Recently they reported on the evolution of this 40-year-old course [35], and identified the substantial use of small group teaching as integral to its success. Several other institutions have reported on their curricular modifications in the past decade [36][37][38]. As an example, Saleh, et al described the introduction of a second-year musculoskeletal sequence at the University of Minnesota [39].…”
Section: Educational Strategies and Implementationmentioning
confidence: 99%
“…Typically, results are compared to historical controls (before institution of the curriculum), often due to ethical concerns regarding the withholding of an educational intervention from part of a class. Bilderback, et al demonstrated improved scores on the Friedman-Bernstein test [36]. Saleh, et al found improved student satisfaction and retention of physical examination skills after 3-4 months [39].…”
Section: Program Evaluationmentioning
confidence: 99%
“…Integrated education and musculoskeletal rotations have been shown to increase physician's knowledge and confidence in treating musculoskeletal complaints [6,19,20]. However, there is minimal literature to support this finding in pediatric residents.…”
Section: Introductionmentioning
confidence: 99%